Security model against worms attack in wireless sensor network. (17th May 2019) - Ojha, Rudra Pratap; Srivastava, Pramod Kumar; Sanyal, Goutam
The wireless sensor network is an innovative category of communication network, which has earned universal attention due to its great potential in application of various areas. This is one of the insecure systems due to attack of worms. In order to efficaciously defend wireless sensor network against worms, we have proposed an epidemic model with two latent periods and vaccination. We have formulated ODE of the model and studied the dynamic behaviour of worm propagation as well as designed a model to secure the system from worm attack. The model has been simulated by MATLAB. In this proposed study, we have determined the basic reproduction number for the study of dynamic performance of worms in the wireless sensor network. The global stability of worm free equilibrium has been established using a Lyapunov function, while the simulation results helped in the validation of the theoretical analysis.